Forecasting economic and financial variables with global VARs - Mohammad Hashem Pesaran; Til Schuermann; L. Vanessa Smith (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper considers the problem of forecasting real and financial macroeconomic variables across a large number of countries in the global economy. To this end a global vector autoregressive (GVAR) model previously estimated over the 1979Q1-2003Q4 period by Dees, de Mauro, Pesaran, and Smith (2007), is used to generate out-of-sample one quarter and four quarters ahead forecasts of real output, inflation, real equity prices, exchange rates and interest rates over the period 2004Q1-2005Q4. Forecasts are obtained for 134 variables from 26 regions made up of 33 countries covering about 90% of world output. The forecasts are compared to typical benchmarks: univariate autoregressive and random walk models. Building on the forecast combination literature, the effects of model and estimation uncertainty on forecast outcomes are examined by pooling forecasts obtained from different GVAR models estimated over alternative sample periods. Given the size of the modeling problem, and the heterogeneity of economies considered industrialised, emerging, and less developed countries as well as the very real likelihood of possibly multiple structural breaks, averaging forecasts across both models and windows makes a significant difference. Indeed the double-averaged GVAR forecasts performed better than the benchmark competitors, especially for output, inflation and real equity prices.
Keywords: C32; C51; C53; 330; forecasting using GVAR; structural breaks and forecasting; average forecasts across models and windows; financial and macroeconomic forecasts; Wirtschaftsprognose; Finanzmarkt; Prognose; Makroökonomik; Strukturbruch; VAR-Modell; Prognoseverfahren; Welt